POSSIBILITIES OF EXPERIMENTAL VERIFICATION OF THE VALIDITY OF URETHRAL PRESSURE PROFILOMETRY - Zatura, Frantisek; Rosenberg, Josef (Biomedical papers, 2006)
Objectives: The aim is to define conditions for exact measurement of urethral pressure profile, to prepare an aparatus and fabricate an artificial urethra for testing measuring catethers. To examine it's qualities by experiment.Methods: We designed a measuring appliance and a specialized software for measuring and evaluating. An experimental phantom of urethra, made from a part of bull's urethra, was used for testing of measurement's validity with use of different measuring catethers. Measurements were 10x repeated within the same position of the catether. Reproducibility of the measurement and stability of the experimental model was tested.Results: Measuring urethra and experimental phantom of urethra succeeded, it was possible to make well reproducible measurements with different measuring catethers and to evaluate their metrologic abilities and limits. Results of our measurements confirmed appointed theoretical conditions of the measurement.Conclusion: Measurements proved that it is possible to simulate the conditions that are similar to physiological conditions and that it is possible to test metrological qualities of compressive profilometry of urethra.
Keywords: Urethral pressure profile/Profilometry/Experimental measurement